Longitudinal associations among food disgust sensitivity, food neophobia, picky eating, and satisfaction with food-related life in adult males and females - Sanle Zhao; Peiyi Wang; Junyu Yin; Hana F. Zickgraf; Jinbo He (Food Quality and Preference, 2026)

Modifying cottonseed protein: Effect of sonication and localized proteolysis on molecular conformation, thermal stability, and solubility - Mokhtar Dabbour; Mohammad Fikry; Sobhi F. Lamlom; Peng Wu; Ronghai He; Arif Rashid; Hafida Wahia; Garba Betchem; Asmaa Hamoda (Food Hydrocolloids, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Periodic seismic velocity variations in shallow marine sediments using decommissioned fiber-optic cable - Zhenghong Song; Xiangfang Zeng; Herbert F. Wang; He Tang; Sidao Ni; Jiangcun Zhou; Ruyu Yan; Qingwen Liu; Tengfei Xu (Earth and Planetary Science Letters, 2026)

Membrane-based advanced oxidation processes for water and wastewater treatment: Advances, trade-offs, and challenges - Caihong Liu; Chi Xiong; Hai Liang; Kun Yang; Andreia F. Faria; Liu Yang; Amauri J. Paula; Hongtao Li; Dan Song; Qiang He; Jun Ma (Chemical Engineering Journal, 2026)

Non-fickian CO2CH4 transport in carbonate composite cores analyzed with fractional-order model and in-situ NMR characterization - Miao Zhang; Lianlin Deng; Bo Ning; Jianlin Guo; He Yuan; Ninghai Fu; Luis F. Ayala (Advances in Water Resources, 2026)

National Evidence of Depth‐Dependent Stabilization and Controls of Soil Organic Carbon in Dryland Croplands - Yuchen Wei; Xin Zhao; Wenting Feng; Hongyong Sun; Jinfeng Chang; Hong Chen; Ji Chen; Xiaowei Guo; Di He; Feng Liu; Alain F. Plante; Zhou Shi; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) underpins agricultural sustainability and the terrestrial carbon cycle, yet its vertical distribution and stabilization across soil depth remain poorly constrained at large spatial scales. Here, we present a nationwide, depth‐resolved dataset of SOC and mineral‐associated organic carbon (MAOC)—the more persistent SOC fraction—from 365 dryland cropland sites across China, sampled to 2 m depth. Contrary to the classic model of exponential SOC decline, 46% of profiles exhibited uniform or increasing SOC and MAOC with depth, highlighting a substantial role of subsoil carbon. MAOC accounted for more than half of total SOC in most layers, but its relative contribution declined below 1 m, challenging the assumption that subsoil carbon is inherently more stable. Clay + silt content was the strongest predictor for SOC, MAOC, and MAOC/SOC across depths, while vegetation productivity, a proxy for carbon inputs, was positively associated with all three. The influence of clay + silt on MAOC accumulation weakened with depth, and the positive interaction between vegetation productivity and clay + silt weakened or diminished from surface soils to deeper layers. These patterns indicate a transition from joint regulation by carbon inputs and mineral surfaces in surface soils toward an increasingly input‐limited regime in deeper layers, as inferred from the depth‐dependent changes in the relative importance of vegetation productivity and fine particle content. National mapping estimated ~19.9 Pg SOC stored within the 0–2 m layer in China's dryland croplands, with 75% below 0.3 m and 60% stabilized as MAOC. These results provide a benchmark for depth‐explicit SOC accounting and highlight the importance of aligning carbon inputs with soil mineralogy to enhance whole‐profile carbon stabilization and climate mitigation.

Ecological functions and bioaugmentation applications of stress-resistant microorganisms under inhibited anaerobic digestion environments - Chao Yang; Pinjing He; Andreia F. Salvador; Wei Peng; Hua Zhang; Haowen Duan; Fan Lü (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Triggering mechanisms and dynamics of an off-season rainfall-induced rock avalanche in the Wumeng Mountains, China - Guiping Xia; Xiaoyi Fan; Ying Zhou; Anjiang He; Jiaqin Chen; Huan Liu; M. F. Hassanein (Landslides, 2026)

A common mantle source for strongly silica-undersaturated magmas: Insights from Zn-Fe isotopes in kimberlites - Ronghua Cai; Andrea Giuliani; Paolo A. Sossi; Tian-Hao Wu; Yongsheng He; D. Graham Pearson; Stephen F. Foley; Jingao Liu (Earth and Planetary Science Letters, 2026)

Anti-asthmatic effects and ingredient annotation of the active fraction from Ganoderma lucidum - Ning Li; Qian He; Cunwu W. Chen; Qun Zhao; Yanfei F. He (Journal of Natural Medicines, 2026)

Heme Iron Polypeptide Resolves Iron-deficiency Anemia in Rats and Mice - Yue He; Jacob S. Shine; Sitara Sriram; Melissa Fraga; Li-Ying Kuo; Jennifer K. Lee; Xiaojing Yuan; Iqbal Hamza; James F. Collins (Biological Trace Element Research, 2026)

Reevaluating the contribution of grain for green program to GPP in the Loess Plateau: Insights from a process-based model - Qiaoli Wu; Xinyang Zhang; Shaoyuan Chen; Trevor F. Keenan; Wei He; Li Wang; Jie Jiang (Agricultural and Forest Meteorology, 2026)

Household investment behavior and environmental impact: How family financial decisions influence carbon emissions in China - Tianzuo Wen; Will W. Qiang; Haowen Luo; Harry F. Lee; Shenjing He (Sustainable Cities and Society, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Clover cover alters soil organic matter composition, diversity, and complexity in apple orchards on the loess plateau: Temporal and vertical variations - Mengfan He; Zhuoliang Liu; Wenle Ni; Shuchen Lei; Huizhen Yin; Miles F. Dyck; Sylvie A. Quideau; Yuanji Wang; Zhilong Duan; Xining Zhao; Huike Li; Xiaolin Song; et al. (Soil and Tillage Research, 2026)

Stakeholder-informed environmental-economic tradeoffs at the farm and forest scale - D. Kaplan; K. Athearn; W.L. Bartels; P. Carton de Grammont; C. Court; F. He; R. Hochmuth; U. Koirala; D. Lee; J. Love; N. Reaver; R. de Rooij; et al. (Journal of Environmental Management, 2026)

Vascular Organoids Derived from Capillary malformation-induced Pluripotent Stem Cells Exhibit Disease-Relevant Phenotypes - Vi Nguyen; Anna Harper; Mackenzie Azuero; Isabella Castellanos; Siwuxie He; Marcelo L. Hochman; Camilla F. Wenceslau; Dong-bao Chen; Anil G. Jegga; Yunguan Wang; Daping Fan; J. Stuart Nelson; et al. (Stem Cell Reviews and Reports, 2026)
Capillary malformation (CM) is a congenital vascular anomaly that affects the skin, mucosa, eye, and brain. A major obstacle to mechanistic and drug screening studies for CM has been the lack of preclinical models. In this study, we established vascular organoids (VOs) generated through the self-assembly of vascular lineages of endothelial cells and smooth muscle cells differentiated from CM-induced pluripotent stem cells (iPSC). Within these VOs induced endothelial cells and smooth muscle cells organized into juxtapositions to form vascular branches. CM patient iPSC-derived VOs showed a higher density of endothelial and smooth muscle cell populations and greater vascular branch lengths as compared with VOs derived from iPSCs generated from healthy skin biopsies. Overall, this study represents the first disease-relevant VO model of CM, providing a valuable platform for future mechanistic studies and drug screening.

A new Myxospora ( Hypocreales, Sordariomycetes ) species from the Tibetan Plateau, China - Shu-Cheng He; Vinodhini Thiyagaraja; Chitrabhanu S. Bhunjun; Ruvishika S. Jayawardena; Putarak Chomnunti; F. Al-Otibi; Yun-Wei Zhao; Qi Zhao; Kevin D. Hyde (New Zealand Journal of Botany, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Wall effects on fluid-structure interaction of tandem flapping foils operating in energy extraction mode - F. Zhao; Z. He; Z. Wang; M.N. Mumtaz Qadri; A. Munir; Y. Dong; H. Tang (Ocean Engineering, 2025)

Increased vascularization of the subchondral region in human osteoarthritic femoral head in the elderly - Yuqi He; Katrin Bundkirchen; Shahed Taheri; Ricarda Stauß; Emmanouil Liodakis; Claudia Neunaber; Arndt F. Schilling; Christian Mühlfeld; Stephan Sehmisch; Tilman Graulich (Histochemistry and Cell Biology, 2025)
This study aimed to quantitatively analyze subchondral vascularization during the progression of osteoarthritis (OA) in the elderly, particularly regarding the timing of initial blood vessel emergence and when their density peaks. A total of 129 independent areas from 43 human femoral heads, obtained through arthroplasty for OA or hemiarthroplasty for fractures, were analyzed. The femoral heads were grouped by Kellgren-Lawrence (KL) grades: KL 1 (6 heads), KL 2 (14 heads), KL 3 (10 heads), and KL 4 (13 heads), and the Mankin score was assessed. Quantitative measurements of blood vessel length 1 mm below the tidemark, cartilage volume and thickness, chondrocyte volume, ECM volume, subchondral bone volume, and bone marrow volume were performed using stereology and immunohistochemistry. The most substantial increase in the characteristics of blood vessels within the subchondral region began at KL 3 and peaked at KL 4. Blood vessel volume increased from 6.71 ± 5.84 mm 3 in group KL 1 to 156.21 ± 138.67 mm 3 in group KL 4 ( p < 0.001). Blood vessel surface area showed an increase from 14.78 ± 9.89 cm 2 (group KL 1) to 125.20 ± 93.18 cm 2 (group KL 4) ( p < 0.001). Likewise, blood vessel length grew from 27.53 m (IQR 13.70–65.41 m) in group KL 1 to 112.03 ± 76.07 m in group KL 4 ( p = 0.001). This study offers deeper insights into the role of vascularization in OA pathophysiology, quantifying subchondral blood vessel characteristics in the femoral head across different OA stages.

Characterizing emotional eating by valence, over-vs under-eating, and contextual factors: A latent profile analysis - Urvashi Dixit; Wesley R. Barnhart; Erica M. Ahlich; Rachel R. Henderson; Anna A. Love; Jinbo He; Hana F. Zickgraf (Appetite, 2025)

Environmental RNA ‐Based Metatranscriptomics as a Novel Biomonitoring Tool: A Case Study of Glyphosate‐Based Herbicide Effects on Freshwater Eukaryotic Communities - Xiaoping He; Takahiro Maruki; Wendy B. Morgado‐Gamero; Rowan D. H. Barrett; Vincent Fugère; Gregor F. Fussmann; Andrew Gonzalez; B. Jesse Shapiro; Melania E. Cristescu (Molecular Ecology, 2025)
Traditional morphology‐ and molecular‐based biodiversity surveys provide essential information on species composition and diversity, but they rarely provide information about the physiological states of organisms, which are key indicators of ecosystem health. Environmental RNA (eRNA) has the potential to significantly enhance biomonitoring by providing insights beyond species detection. Recent studies suggest that extra‐organismal RNA released into the environment could help identify differentially expressed genes of single species. However, the feasibility of eRNA‐based metatranscriptomics on complex environmental samples, containing both extra‐organismal and organismal eukaryotic RNA, remains untested due to numerous experimental and analytical challenges. In this study, we explored the potential of eRNA‐based metatranscriptomics, enriched for eukaryotes, as a tool to monitor environmental stress. We used outdoor mesocosms to examine the acute effects of a glyphosate‐based herbicide (GBH) on gene transcription across diverse freshwater eukaryotic taxa. Our metatranscriptomics data revealed diverse eukaryotic taxa spanning multiple trophic levels, including phytoplankton, zooplankton, ciliates, and aquatic insects. GBH treatment significantly altered the relative transcript abundances of most eukaryotic classes, with longer‐lived taxa demonstrating greater tolerance compared to shorter‐lived taxa. Differential expression analysis showed more gene downregulation than upregulation in response to GBH, likely due to its acute toxicity. Many differentially expressed genes were involved in molecular pathways associated with responses to GBH exposure, such as oxidative stress response and detoxification. Our results demonstrate that eRNA‐based metatranscriptomics captures transcriptional signals from diverse aquatic eukaryotic taxa, providing insights into functional gene expression. As such, its application to support environmental monitoring of aquatic ecosystems warrants further exploration.

Divergent effect of the freeze–thaw process on soil moisture dynamics in an alpine region of the northeast Qinghai-Tibet plateau - Tiaoxue Lu; Linshan Yang; Jingru Wang; Xingyi Zou; Wanghan He; Jan F. Adamowski; Qi Feng (CATENA, 2025)

Phenotypic prevalence index: Diversity of polyphosphate-accumulating organisms (PAOs) and insights in unknown PAOs revealed by combined fluorescence-activated cell sorting (FACS) and 16S rRNA gene sequencing - Peisheng He; Yuan Yan; Jangho Lee; IL Han; Guangyu Li; Fabrizio Sabba; Zhen Jia; George F. Wells; April Z. Gu (Water Research, 2025)

Effects of the interior conductivity on Mercury's field-aligned currents - Z. Shi; S. Fatemi; Z.J. Rong; F. He; Y. Wei (Icarus, 2025)

Maximizing membrane antifouling potential: The impact of fluoride positioning in multifunctional designs - Caihong Liu; Rui Gao; Xiao Wang; Andreia F. Faria; Liu Yang; Bin Zhang; Qiang He (Water Research, 2025)

Corrigendum to “Questionnaire-assessed atypical sensory sensitivity is prospectively related to higher ARFID psychopathology, higher food neophobia, and lower satisfaction with food-related life in an online sample of Chinese older adults” [Food Quality and Preference 122 (2025) 105303] - Yueyang Xiao; Jiayi Han; Hana F. Zickgraf; Wesley R. Barnhart; Yiqing Zhao; Jinbo He (Food Quality and Preference, 2025)

Feline gastrointestinal eosinophilic sclerosing fibroplasia in a young ragdoll cat: with surgical management - Jindong Gao; Yuning Li; Yang Xie; Md. F. Rahim; Md. F. Kulyar; Quan Mo; Jianzhong He; Mengdi Zhang; Xing Wu; Jinhua Yin (Veterinary Research Communications, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A latent class analysis of negative emotional eating in bariatric surgery candidates - Urvashi Dixit; Anna A. Love; Rachel R. Henderson; Erica Ahlich; Jinbo He; Andrea Rigby; Hana F. Zickgraf (Appetite, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

Ultrafast separation of Nd and Dy from Co by modified mesoporous silica with a novel phosphate group ligand - Yilai Zhong; Zengyuan Li; Jianchun Qin; Wenlong Li; Chunlin He; Lifeng Chen; Xiangbiao Yin; Mohammed F. Hamza; Yuezhou Wei; Shunyan Ning (Journal of Water Process Engineering, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Fine mapping of the unique Ur-11 gene conferring broad resistance to the rust pathogen of common bean - Giseli Valentini; Oscar P. Hurtado-Gonzales; Larissa F. S. Xavier; Ruifeng He; Upinder Gill; Qijian Song; Marcial A. Pastor-Corrales (Theoretical and Applied Genetics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Salinity-redox covariation in Mississippian Bowland Shale (Craven Basin, UK) controlled by eustasy and climate - Yu Jiao; Joseph F. Emmings; Lian Zhou; Thomas J. Algeo; Lanping Feng; Tao He; Jinhua Liu; Daqian Zhang; Jianping Wang (Chemical Geology, 2025)

Genomic determinants of biological age estimated by deep learning applied to retinal images - Yu Huang; Mohammad Ghouse Syed; Ruiye Chen; Cong Li; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Shulin Tang; Jing Liu; Shunming Liu; Sundar Srinivasan; et al. (GeroScience, 2025)
With the development of deep learning (DL) techniques, there has been a successful application of this approach to determine biological age from latent information contained in retinal images. Retinal age gap (RAG) defined as the difference between chronological age and predicted retinal age has been established previously to predict the age-related disease. In this study, we performed discovery genome-wide association analysis (GWAS) on the RAG using the 31,271 UK Biobank participants and replicated our findings in 8034 GoDARTS participants. The genetic correlation between RAGs predicted from the two cohorts was 0.67 ( P = 0.021). After meta-analysis, we found 13 RAG loci which might be related to retinal vessel density and other aging processes. The SNP-wide heritability ( h 2 ) of RAG was 0.15. Meanwhile, by performing Mendelian randomization analysis, we found that glycated hemoglobin, inflammation hemocytes, and anemia might be associated with accelerated retinal aging. Our study explored the biological implications and molecular-level mechanism of RAG, which might enable causal inference of the aging process as well as provide potential pharmaceutical intervention targets for further treatment. Graphical Abstract

Negative emotional eating patterns in Chinese adolescents: A replication and longitudinal extension with latent profile and transition analyses - Hongbin Weng; Wesley R. Barnhart; Hana F. Zickgraf; Urvashi Dixit; Yawei Cheng; Gui Chen; Jinbo He (Appetite, 2025)

Coupled effects of iron (hydr)oxides and clay minerals on the heterogeneous oxidation of aqueous Mn(II) and crystallization of manganese (hydr)oxides - Yixuan Yang; Qingze Chen; Jing Liu; Jieqi Xing; Yiping Yang; Runliang Zhu; Hongping He; Michael F. Hochella Jr. (Geochimica et Cosmochimica Acta, 2025)

Questionnaire-assessed atypical sensory sensitivity is prospectively related to higher ARFID psychopathology, higher food neophobia, and lower satisfaction with food-related life in an online sample of Chinese older adults - Yueyang Xiao; Jiayi Han; Hana F. Zickgraf; Wesley R. Barnhart; Yiqing Zhao; Jinbo He (Food Quality and Preference, 2025)

Sweat gland-inspired skin soft actuators of the liquid crystal elastomer enabled by 3D printing - Zhenhua He; Saihua Jiang; Jianji Wang; Nour F. Attia; Dai Kang; Gang Zhou; Shu Xiao (Chemical Engineering Journal, 2025)

Circulating small extracellular vesicles as blood-based biomarkers of muscle health in aging nonhuman primates - Shalini Mishra; Ashish Kumar; Yangen He; Yixin Su; Sangeeta Singh; Mark F. Santos; Rakesh Singh; Jingyun Lee; Cristina M. Furdui; Carol A. Shively; Stephen B. Kritchevsky; Thomas C. Register; et al. (GeroScience, 2024)
Age-associated loss of muscle mass and function and subsequent mobility decline define poor health outcomes, reduced quality of life, and mortality risk. The rate and extent of aging-related muscle loss varies across older adults. It is challenging to understand the molecular pathogenesis of mobility decline, as anthropometric and imaging techniques, primarily used in muscle function assessment, do not offer much molecular information. Small extracellular vesicles (sEV) are lipid membrane-bound, nano-sized (≤ 200 nm) vesicles which carry a wide array of biomolecules as their cargo. sEV contain cell/tissue-specific signatures on their surface and can be isolated from biofluids. These properties pose sEV as a minimally invasive means to monitor the functional and biological health of difficult-to-access tissues, establishing them as a promising liquid biopsy tool. Here, we first isolated skeletal muscle-derived sEV (sEV SKM ) from the serum of vervet monkeys (16 to < 25 years old) using alpha sarcoglycan (SGCA) as a muscle-specific sEV surface marker. sEV SKM were extensively characterized for size, concentration, purity, and specificity. Further, sEV SKM isolated from young (11–15 years) and old (25–29 years) monkeys’ serum were characterized for oxidized proteins by mass spectrometry and miRNAs by small-RNAseq. Notably, the analysis of oxidized proteins indicated perturbation of metabolic pathways, actin cytoskeleton, muscle cytoskeleton regulation, and HIF-1 signaling in older monkeys. Furthermore, small-RNAseq analysis identified differential expression of several miRNAs regulating metabolic pathways, inflammation, and stress signaling. Altogether, these results suggest that it is feasible to isolate sEV SKM and use them to identify molecular biomarkers that reflect the physiological state of muscle tissue.

The evolution of amino acids under asteroidal aqueous alteration - Y.Y. He; S. Bernard; M. Lecasble; J.-C. Viennet; I. Criouet; D. Boulesteix; N. Khodorova; L. Delbes; M. Guillaumet; F. Baudin; B. Laurent; A. Buch; et al. (Geochimica et Cosmochimica Acta, 2024)

Constructing Ce–OH groups on CeO2 for enhancing removal and recovery of uranium from wastewater and seawater - Linxin Zheng; Ningchao Zheng; Zhizeng Pan; Guang Gao; Chao He; Xinran Mou; Xiangbiao Yin; Shunyan Ning; Mohammed F. Hamza; Yuezhou Wei (Chemosphere, 2024)

Per- and polyfluoroalkyl substances (PFAS) in floor dust from different indoor environments in Australia: Levels, variation, and human exposure risks - Zongrui Li; Zubaria Ishaq; Chang He; Andrew P.W. Banks; Jennifer Bräunig; Phong K. Thai; Ayomi Jayarathne; Jochen F. Mueller; Xianyu Wang (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cryogenic vacuum distillation vs Cavitron methods in ecohydrology: Extraction protocol effects on plant water isotopic values - Hongxiu Wang; Haiyang Yu; Dong He; Min Li; Bingcheng Si; Jeffrey J. McDonnell; Magali F. Nehemy (Journal of Hydrology, 2024)

Time-varying associations of patient and tumor characteristics with cancer survival: an analysis of SEER data across 14 cancer sites, 2004–2017 - Emily K. Roberts; Lingfeng Luo; Alison M. Mondul; Mousumi Banerjee; Christine M. Veenstra; Angela B. Mariotto; Matthew J. Schipper; Kevin He; Jeremy M. G. Taylor; Andrew F. Brouwer (Cancer Causes & Control, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

LP-18 Simultaneous determination of 5 kinds of virulent mushroom toxinsin human whole blood by ultra performance liquid chromatography- tandem mass spectrometry - L. He; Y. Dong; F. Wang; X. Sun (Toxicology Letters, 2024)

P01-21 Determination of 9 Bufotoxins by LC-MS/MS - Y. Dong; L. He; F. Wang (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Assessing daily patterns in stimulant use during the COVID-19 pandemic in Melbourne, Australia using wastewater analysis - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Phong Thai; Chang He; Fahad Ahmed; Qiuda Zheng; Phil M. Choi; Jake W. O’Brien; Jochen F. Mueller (Journal of Hazardous Materials, 2024)

Age-associated proteins explain the role of medial temporal lobe networks in Alzheimer’s disease - Adam Turnbull; Yejin Kim; Kai Zhang; Xiaoqian Jiang; Zihuai He; Victor W. Henderson; F. Vankee Lin (GeroScience, 2024)

Novel phosphate functionalized sodium alginate hydrogel for efficient adsorption and separation of Nd and Dy from Co - Yilai Zhong; Shunyan Ning; Kun Wu; Zengyuan Li; Xinpeng Wang; Chunlin He; Toyohisa Fujita; Ji Wang; Lifeng Chen; Xiangbiao Yin; Mohammed F. Hamza; Yuezhou Wei (Journal of Environmental Management, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

An early Paleozoic accumulation-foundering cycle of ultramafic cumulates in the Harlik arc and its implications for continental crustal growth in the Altaids - Liang Li; Wenjiao Xiao; Brian F. Windley; Guochun Zhao; He Yang; Miao Sang; Xiaoliang Jia (Lithos, 2023)

Paleo-lake evolution influenced by tectonic processes and climate changes in the Hetao Basin during the late Quaternary - Haoyue Zhang; Xujiao Zhang; Peisheng Ye; Xiangli He; Liyun Jia; Junxiang Zhao; Pat J.-F. Yeh (CATENA, 2023)

Bisphenols and phthalates in Australian wastewater: A statistical approach for estimating contributions from diffuse and point sources - Belinda Moore; Chang He; Emma Knight; Jochen F. Mueller; Benjamin Tscharke (Water Research, 2023)

Direct injection liquid chromatography-tandem mass spectrometry as a sensitive and high-throughput method for the quantitative surveillance of antimicrobials in wastewater - Jinglong Li; Katja M. Shimko; Chang He; Brad Patterson; Richard Bade; Ryan Shiels; Jochen F. Mueller; Kevin V. Thomas; Jake W. O'Brien (Science of The Total Environment, 2023)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Land use and rainfall influences on bacterial levels and sources in stormwater ponds - Mina Shahirnia; Cuauhtémoc Tonatiuh Vidrio-Sahagún; Jianxun He; Caterina Valeo; Bert van Duin; Megan Beaudry; Norman F. Neumann (Environmental Science and Pollution Research, 2023)

Tightly coupled Ca-Zn-Sr isotope co-variations in basalts caused by recycled calcium carbonate in the mantle source - Detao He; Yongsheng Liu; Frédéric Moynier; Stephen F. Foley; Chunfei Chen; Yangtao Zhu; Xinting Lü; Ganglan Zhang; Keqing Zong (Chemical Geology, 2023)

Fracture Toughness Anisotropy in Shale Under Deep In Situ Stress Conditions - Q. Zhou; H. P. Xie; Z. M. Zhu; R. He; H. J. Lu; Z. D. Fan; X. F. Nie; L. Ren (Rock Mechanics and Rock Engineering, 2023)

P24-42: A new generation of fully human anti-CTLA-4 heavy chain-only, Porustobart, shows superior safety in nonclinical study and clinical trials - J. Rong; L. Ding; F. Chen; J. Zhao; Y. He; Y. Rong; V. Chen (Toxicology Letters, 2023)

Negative emotional eating patterns among American university students: A replication study - Urvashi Dixit; Jinbo He; Matthew Whited; Jordan M. Ellis; Hana F. Zickgraf (Appetite, 2023)

Highly efficiently selective separation of zirconium from scandium by TRPO modified adsorbent - Yilai Zhong; Shunyan Ning; Xinpeng Wang; Chunlin He; Toyohisa Fujita; Mohammed F. Hamza; Yuezhou Wei (Journal of Environmental Chemical Engineering, 2023)

Plate convergence controls long-term full-depth circulation of the South China Sea - Shaoru Yin; F. Javier Hernández-Molina; Lin Lin; Min He; Jinyao Gao; Jiabiao Li (Marine Geology, 2023)

B-Cell-Activating Factor Contributes to Elevation of the Content of Regulatory B Cells in Neonatal Sepsis - W. Liao; H. Xiao; J. He; L. Huang; Y. Liao; J. Qin; Q. Yang; F. Ma; S. Li (Bulletin of Experimental Biology and Medicine, 2023)

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Global photosynthetic capacity of C3 biomes retrieved from solar-induced chlorophyll fluorescence and leaf chlorophyll content - Yihong Liu; Jing M. Chen; Liming He; Rong Wang; Nicholas G. Smith; Trevor F. Keenan; Cheryl Rogers; Wenyu Li; Jiye Leng (Remote Sensing of Environment, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

Electrochemical disinfection may increase the spread of antibiotic resistance genes by promoting conjugal plasmid transfer - Hua Li; Arnaud Dechesne; Zhiming He; Marlene Mark Jensen; Hai Liang Song; Barth F. Smets (Science of The Total Environment, 2023)

Modelling the impacts of inhibitors and fertilizer placement on maize yield and ammonia, nitrous oxide and nitrate leaching losses in southwestern Ontario, Canada - Rong Jiang; Jingyi Yang; Craig F. Drury; Brian B. Grant; Ward N. Smith; Wentian He; Daniel W. Reynolds; Ping He (Journal of Cleaner Production, 2023)

Design and Applicability of an Abandoned Coal Mine Roadway for Landfill Sites - H. F. Lu; A. C. Wei; Z. A. He; F. Xu; X. X. Kong; Q. Z. Zhang (Water, Air, & Soil Pollution, 2023)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Cracking Behavior and Mechanism of Igneous Rocks Under Open-Ended Microwave Irradiation - X. B. Zhao; Q. H. Zhao; Y. L. Zheng; L. He; J. L. He; G. F. Zhao; H. Li (Rock Mechanics and Rock Engineering, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

Fungal Endophytes Help Grasses to Tolerate Sap-Sucking Herbivores Through a Hormone-Signaling System - Yali He; Taixiang Chen; Haijuan Zhang; James F. White; Chunjie Li (Journal of Plant Growth Regulation, 2022)

Synthesis of 2-oxoquinoline derivatives as dual pim and mTORC protein kinase inhibitors - Giri R. Gnawali; Koichi Okumura; Karolina Perez; Rosa Gallagher; Julia Wulfkuhle; Emanuel F. Petricoin; Sathish Kumar Reddy Padi; Jeremiah Bearss; Zhiyong He; Wei Wang; Andrew S. Kraft (Medicinal Chemistry Research, 2022)

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

The Ocean's labile DOC supply chain - Mary Ann Moran; Frank X. Ferrer‐González; He Fu; Brent Nowinski; Malin Olofsson; McKenzie A. Powers; Jeremy E. Schreier; William F. Schroer; Christa B. Smith; Mario Uchimiya (Limnology and Oceanography, 2022)
Microbes of the surface ocean release, consume, and exchange labile metabolites at time scales of minutes to days. The details of this important step in the global carbon cycle remain poorly resolved, largely due to the methodological challenges of studying a diverse pool of metabolites that are produced and consumed nearly simultaneously. In this perspective, a new compilation of published data builds on previous studies to obtain an updated estimate of the fraction of marine net primary production that passes through the labile dissolved organic carbon (DOC) pool. In agreement with previous studies, our data mining and modeling approaches hypothesize that about half of ocean net primary production is processed through the labile DOC pool. The fractional contributions from three major sources are estimated at 0.4 for living phytoplankton, 0.4 for dead and dying phytoplankton, and 0.2 for heterotrophic microbes and mesoplankton.

The premature decay of rifting processes in the northern South China Sea (38–33.9 Ma): insight from 3D seismic and its interpretation of the Lufeng Sag of the Pearl River Mouth Basin - B. S. Ma; J. W. Ge; G. H. Wu; J. F. Qi; F. Yu; S. Chen; W. G. He (Australian Journal of Earth Sciences, 2022)

Epichloë Endophyte Improves Ergot Disease Resistance of Host (Achnatherum inebrians) by Regulating Leaf Senescence and Photosynthetic Capacity - Haijuan Zhang; Xiuzhang Li; James F. White; Xuekai Wei; Yali He; Chunjie Li (Journal of Plant Growth Regulation, 2022)

Contrasting Early Palaeozoic provenance of the Yemaquan and Harlik arcs in the SW Altaids (NW China): identification of cryptic sutures in accretionary orogens - Liang Li; Wenjiao Xiao; Brian F. Windley; Qigui Mao; Xiaoliang Jia; He Yang; Zhou Tan; Miao Sang; Jingmin Gan; Nijiati Abuduxun (International Geology Review, 2021)

Bi-allelic truncating variants in CFAP206 cause male infertility in human and mouse - Qunshan Shen; Guillaume Martinez; Hongbin Liu; Julie Beurois; Huan Wu; Amir Amiri-Yekta; Dan Liang; Zine-Eddine Kherraf; Marie Bidart; Caroline Cazin; Tristan Celse; Véronique Satre; et al. (Human Genetics, 2021)

Biotic signals associated with benthic impacts of salmon farms from eDNA metabarcoding of sediments - Xiaoping He; Scott R. Gilmore; Terri F. Sutherland; Mehrdad Hajibabaei; Kristina M. Miller; Kristen M. Westfall; Jan Pawlowski; Cathryn L. Abbott (Molecular Ecology, 2021)
Environmental DNA (eDNA) metabarcoding can rapidly characterize the composition and diversity of benthic communities, thus it has high potential utility for routine assessments of benthic impacts of marine finfish farming. In this study, 126 sediment grab samples from 42 stations were collected at six salmon farms in British Columbia, Canada. Benthic community changes were assessed by both eDNA metabarcoding of metazoans and macrofaunal polychaete surveys. The latter was done by analysing 11,466 individuals using a combination of morphology‐based taxonomy and DNA barcoding. Study objectives were to: (i) compare biotic signals associated with benthic impacts of salmon farming in the two data sources, and (ii) identify potential eDNA indicators to facilitate monitoring in Canada. Alpha diversity parameters were consistently reduced near fish cage edge and negatively correlated with pore‐water sulphide concentration, with coefficients ranging from −0.62 to −0.48. Although Polychaeta are a common indicator group, the negative correlation with pore‐water sulphide concentration was much stronger for Nematoda OTU richness (correlation coefficient: −0.86) than for Polychaeta (correlation coefficient: −0.38). Presence/absence of Capitella generally agreed well between the two methods despite that they differed in the volume of sediments sampled and the molecular marker used. Multiple approaches were used to identify OTUs related to organic enrichment statuses. We demonstrate that eDNA metabarcoding generates biotic signals that could be leveraged for environmental assessment of benthic impacts of fish farms in multiple ways: both alpha diversity and Nematoda OTU richness could be used to assess the spatial extent of impact, and OTUs related to organic enrichment could be used to develop local biotic indices.

Enhanced biogas production at mesophilic and thermophilic temperatures from a slaughterhouse waste with zeolite as ammonia adsorbent - B. Fatima; R. Liaquat; U. Farooq; A. Jamal; M. I. Ali; F.-J. Liu; H. He; H. Guo; M. Urynowicz; Z. Huang (International Journal of Environmental Science and Technology, 2021)

Application of ornithine-induced regulation in yield formation, grain quality and aroma of fragrant rice - H. W. Luo; P. P. Xing; J. H. Liu; R. F. Lai; L. X. He; T. T. Zhang; X. R. Tang (Cereal Research Communications, 2020)

Models and measurements of seven years of evapotranspiration on a high elevation site on the Central Tibetan Plateau - Li-hui Wang; Xiao-bo He; Jakob F. Steiner; Dong-wei Zhang; Jin-kui Wu; Shao-yong Wang; Yong-jian Ding (Journal of Mountain Science, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Study on crack propagation and shear behavior of weak muddy intercalations submitted to wetting-drying cycles - L. P. He; J. Y. Yu; Q. J. Hu; Q. J. Cai; M. F. Qu; T. J. He (Bulletin of Engineering Geology and the Environment, 2020)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

Composition, physicochemical properties of pea protein and its application in functional foods - Z. X. Lu; J. F. He; Y. C. Zhang; D. J. Bing (Critical Reviews in Food Science and Nutrition, 2020)

Influence of RNA interference-mediated reduction of Or11 on the expression of transcription factor Kr-h1 in Apis mellifera drones - J. F. Liu; X. J. Wan; Z. L. Wang; X. J. He; Z. J. Zeng (Insectes Sociaux, 2020)

Causes of slowing‐down seasonal CO 2 amplitude at Mauna Loa - Kai Wang; Yilong Wang; Xuhui Wang; Yue He; Xiangyi Li; Ralph F. Keeling; Philippe Ciais; Martin Heimann; Shushi Peng; Frédéric Chevallier; Pierre Friedlingstein; Stephen Sitch; et al. (Global Change Biology, 2020)
Changing amplitude of the seasonal cycle of atmospheric CO 2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO 2 record, shows an increasing SCA before the 1980s ( p 2 fertilization. This challenges the view that CO 2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO 2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs.

Correction to: Transcriptional and metabolite analysis reveal a shift in direct and indirect defences in response to spider‑mite infestation in cucumber (Cucumis sativus) - Jun He; Harro J. Bouwmeester; Marcel Dicke; Iris F. Kappers (Plant Molecular Biology, 2020)

Transcriptional and metabolite analysis reveal a shift in direct and indirect defences in response to spider-mite infestation in cucumber (Cucumis sativus) - Jun He; Harro J. Bouwmeester; Marcel Dicke; Iris F. Kappers (Plant Molecular Biology, 2020)
Key message Cucumber plants adapt their transcriptome and metabolome as result of spider mite infestation with opposite consequences for direct and indirect defences in two genotypes. Abstract Plants respond to arthropod attack with the rearrangement of their transcriptome which lead to subsequent phenotypic changes in the plants’ metabolome. Here, we analysed transcriptomic and metabolite responses of two cucumber ( Cucumis sativus ) genotypes to chelicerate spider mites ( Tetranychus urticae ) during the first 3 days of infestation. Genes associated with the metabolism of jasmonates, phenylpropanoids, terpenoids and l -phenylalanine were most strongly upregulated. Also, genes involved in the biosynthesis of precursors for indirect defence-related terpenoids were upregulated while those involved in the biosynthesis of direct defence-related cucurbitacin C were downregulated. Consistent with the observed transcriptional changes, terpenoid emission increased and cucurbitacin C content decreased during early spider-mite herbivory. To further study the regulatory network that underlies induced defence to spider mites, differentially expressed genes that encode transcription factors (TFs) were analysed. Correlation analysis of the expression of TF genes with metabolism-associated genes resulted in putative identification of regulators of herbivore-induced terpenoid, green-leaf volatiles and cucurbitacin biosynthesis. Our data provide a global image of the transcriptional changes in cucumber leaves in response to spider-mite herbivory and that of metabolites that are potentially involved in the regulation of induced direct and indirect defences against spider-mite herbivory.

Gene-environment regulation of chamber-specific maturation during hypoxemic perinatal circulatory transition - Yan Zhao; Xuedong Kang; Alexander Barsegian; Jian He; Alejandra Guzman; Ryan P. Lau; Reshma Biniwale; Madhuri Wadhra; Brian Reemtsen; Meena Garg; Nancy Halnon; Fabiola Quintero-Rivera; et al. (Journal of Molecular Medicine, 2020)

Fate of 2,4,6-Tribromophenol in Soil Under Different Redox Conditions - Xiong Jia; Wenji Wang; Yao Yao; Yujie He; Philippe F.-X. Corvini; Rong Ji (Bulletin of Environmental Contamination and Toxicology, 2020)

Repression of the transcriptional activity of ERRα with sequence-specific DNA-binding polyamides - Chien-yu Chen; Yang Li; Tiezheng Jia; Lina He; Alissa A. Hare; Amanda Silberstein; John Gallagher; Thomas F. Martinez; Joseph W. Stiles; Bogdan Olenyuk; Peter B. Dervan; Bangyan L. Stiles (Medicinal Chemistry Research, 2020)

Soil microbial biomass increases along elevational gradients in the tropics and subtropics but not elsewhere - Xianjin He; Enqing Hou; G. F. Veen; M. D. Farnon Ellwood; Paul Dijkstra; Xinghua Sui; Shuang Zhang; Dazhi Wen; Chengjin Chu (Global Ecology and Biogeography, 2020)
Aim Our aim is to use elevational gradients to quantify the relationship between temperature and ecosystem functioning. Ecosystem functions such as decomposition, nutrient cycling and carbon storage are linked with the amount of microbial biomass in the soil. Previous studies have shown variable relationships between elevation and soil microbial biomass (SMB). Understanding the biological mechanisms linking SMB with elevational gradients will shed light on the environmental impacts of global warming. Location Global. Time period 2002–2018. Major taxa studied Soil microbes. Method We performed a global meta‐analysis of the relationships between SMB and elevation. Data were collected from 59 studies of 73 elevational transects from around the world. Results We found no consistent global relationship between SMB and elevation. SMB increased significantly with elevation in the tropics and subtropics, but not in other climate zones. However, we found consistent positive relationships between SMB, soil organic carbon and total nitrogen concentrations. Main conclusions Our results suggest that global warming will impact tropical and subtropical ecosystems more severely than colder regions. Tropical ecosystems, already at risk from species extinctions, will likely experience declines in SMB as the climate warms, resulting in losses of fundamental ecosystem functions such as nutrient cycling and carbon storage.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The transcription factor CsBzip10 controls vegetative growth, asexual development, appressorium formation and pathogenicity in the Rosa chinensis anthracnose fungus Colletotrichum siamense - R. F. Liu; He Li (Australasian Plant Pathology, 2019)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

Phenotypic Characterization of Canadian Barley Advanced Breeding Lines for Multiple Disease Resistance - M. Osman; X. He; F. Capettini; J. Helm; P.K. Singh (Cereal Research Communications, 2019)

Improved estimates of global terrestrial photosynthesis using information on leaf chlorophyll content - Xiangzhong Luo; Holly Croft; Jing M. Chen; Liming He; Trevor F. Keenan (Global Change Biology, 2019)
The terrestrial biosphere plays a critical role in mitigating climate change by absorbing anthropogenic CO 2 emissions through photosynthesis. The rate of photosynthesis is determined jointly by environmental variables and the intrinsic photosynthetic capacity of plants (i.e. maximum carboxylation rate; ). A lack of an effective means to derive spatially and temporally explicit has long hampered efforts towards estimating global photosynthesis accurately. Recent work suggests that leaf chlorophyll content (Chl leaf ) is strongly related to , since Chl leaf and are both correlated with photosynthetic nitrogen content. We used medium resolution satellite images to derive spatially and temporally explicit Chl leaf , which we then used to parameterize within a terrestrial biosphere model. Modelled photosynthesis estimates were evaluated against measured photosynthesis at 124 eddy covariance sites. The inclusion of Chl leaf in a terrestrial biosphere model improved the spatial and temporal variability of photosynthesis estimates, reducing biases at eddy covariance sites by 8% on average, with the largest improvements occurring for croplands (21% bias reduction) and deciduous forests (15% bias reduction). At the global scale, the inclusion of Chl leaf reduced terrestrial photosynthesis estimates by 9 PgC/year and improved the correlations with a reconstructed solar‐induced fluorescence product and a gridded photosynthesis product upscaled from tower measurements. We found positive impacts of Chl leaf on modelled photosynthesis for deciduous forests, croplands, grasslands, savannas and wetlands, but mixed impacts for shrublands and evergreen broadleaf forests and negative impacts for evergreen needleleaf forests and mixed forests. Our results highlight the potential of Chl leaf to reduce the uncertainty of global photosynthesis but identify challenges for incorporating Chl leaf in future terrestrial biosphere models.

Controlling factors of reservoir quality in low-permeability reservoir within a sequence stratigraphic framework: a case study of the lower Jurassic sandstones in the Northern margin of the Qaidam Basin, China - C.-Q. Ren; X.-Z. Gao; Y.-S. Zhang; B. Wang; Z.-S. Hou; J.-M. Li; F.-G. He (Australian Journal of Earth Sciences, 2019)

Responses of foraminifera communities to aquaculture‐derived organic enrichment as revealed by environmental DNA metabarcoding - Xiaoping He; Terri F. Sutherland; Jan Pawlowski; Cathryn L. Abbott (Molecular Ecology, 2019)
Current monitoring methods to assess benthic impacts of marine finfish aquaculture are based on complex biological indices and/or geochemistry data. The former requires benthic macrofauna morpho‐taxonomic characterization that is time‐ and cost‐intensive, while the latter provides rapid assessment of the organic enrichment status of sediments but does not directly measure biotic impacts. In this study, sediment samples were collected from seven stations at six salmon farms in British Columbia, Canada, and analyzed for geochemical parameters and by eDNA metabarcoding to investigate linkages between geochemistry and foraminifera. Sediment texture across farm sites ranged from sand to silty loam, while the maximum sediment pore‐water sulphide concentration at each site ranged from 1,000 to 13,000 μM. Foraminifera alpha diversity generally increased with distance from cage edge. Adonis analyses revealed that farm site explained the most variation in foraminifera community, followed by sediment type, enrichment status, and distance from cage edge. Farm‐specific responses were observed in diversity analyses, taxonomic difference analyses, and correlation analyses. Results demonstrated that species diversity and composition of foraminifera characterized by eDNA metabarcoding generated signals consistent with benthic biodiversity being impacted by finfish farming activities. This substantiates the validity of eDNA metabarcoding for augmenting current approaches to benthic impact assessments by providing more cost‐effective and practicable biotic measures than traditional morpho‐taxonomy. To capitalize on this potential, further work is needed to design a new nomogram that combines eDNA metabarcoding data and geochemistry data to enable accurate monitoring of benthic impacts of fish farming in a time‐ and cost‐efficient way.

A method for cell suspension culture and plant regeneration of Angelica sinensis (Oliv.) Diels - Y. H. Zhang; Y. Y. Lu; C. Y. He; S. F. Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Draft genome of the fungicidal biological control agent Burkholderia anthina strain XXVI - S. de los Santos-Villalobos; J. M. Kremer; F. I. Parra-Cota; A. C. Hayano-Kanashiro; L. F. García-Ortega; S. K. Gunturu; J. M. Tiedje; S. Y. He; J. J. Peña-Cabriales (Archives of Microbiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Susceptibility profile of echinocandins, azoles and amphotericin B against yeast phase of Talaromyces marneffei isolated from HIV-infected patients in Guangdong, China - H.-L. Lei; L.-H. Li; W.-S. Chen; W.-N. Song; Y. He; F.-Y. Hu; X.-J. Chen; W.-P. Cai; X.-P. Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Structure–function relationships during segregated and integrated network states of human brain functional connectivity - Makoto Fukushima; Richard F. Betzel; Ye He; Martijn P. van den Heuvel; Xi-Nian Zuo; Olaf Sporns (Brain Structure and Function, 2018)

The high prevalence of pathogenic Vibrio harveyi with multiple antibiotic resistance in scale drop and muscle necrosis disease of the hybrid grouper, Epinephelus fuscoguttatus (♀) × E. lanceolatus (♂), in China - Z M Zhu; C F Dong; S P Weng; J G He (Journal of Fish Diseases, 2018)
Scale drop and muscle necrosis disease with high mortality widely occurred recently in the hybrid grouper ( Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂), a crucial cultured marine fish species in China. In this study, 30 Harveyi clade isolates of 27 Vibrio harveyi strains were isolated from diseased hybrid groupers in the south‐east and north‐east coastal areas of China. A total of 22 V. harveyi strains were determined to be pathogenic, and most challenged fish died within 2 days of infection; surviving individuals exhibited scale drop and deep dermal lesions as naturally diseased fish. Although five typical virulence genes, including luxR , toxR Vh , chiA , serine protease and vhh widely existed in V. harveyi , no obvious correlation was established between virulent strains and virulence genes harboured in them. Furthermore, multiple antibiotic resistance was widely exhibited in Harveyi clade strains, particularly for penicillins, polypeptides, lincomycins, acetylspiramycin, streptomycin, metronidazole and bacitracin. And the multiple antibiotic resistance indices were gradually decreased from southern to northern areas of China. This study demonstrated that the pathogenic V. harveyi with multiple antibiotic resistance is highly prevalent in hybrid grouper in China, which requires particular attention.

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Leaf photosynthetic rate and mesophyll cell anatomy changes during ontogenesis in backcrossed indica × japonica rice inbred lines - Wenxing He; Shunsuke Adachi; Rowan F. Sage; Taiichiro Ookawa; Tadashi Hirasawa (Photosynthesis Research, 2017)

Size effects on granite behavior under unloading rockburst test - F. Zhao; M. C. He (Bulletin of Engineering Geology and the Environment, 2017)

Molecular characterization of a novel bipartite begomovirus isolated from Lycianthes biflora in China - Y. F. Tang; Z. F. He; J. K. Brown; X. M. She; G. B. Lan (Archives of Virology, 2017)

Effect of Feeding and Withdrawal of Vanadium and Vitamin C on Egg Quality and Vanadium Residual Over Time in Laying Hens - J. P. Wang; K. R. He; X. M. Ding; S. P. Bai; Q. F. Zeng; K. Y. Zhang (Biological Trace Element Research, 2017)

Strategies for Creating Prescribed Hydraulic Fractures in Cave Mining - Q. He; F. T. Suorineni; J. Oh (Rock Mechanics and Rock Engineering, 2017)

Reply to the comments on “Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust” - Rui Wang; William J. Collins; Roberto F. Weinberg; Jeremy P. Richards; Wen-yan He (Contributions to Mineralogy and Petrology, 2017)

Review of Hydraulic Fracturing for Preconditioning in Cave Mining - Q. He; F. T. Suorineni; J. Oh (Rock Mechanics and Rock Engineering, 2016)

Effects of alkaline and bioorganic amendments on cadmium, lead, zinc, and nutrient accumulation in brown rice and grain yield in acidic paddy fields contaminated with a mixture of heavy metals - Huaidong He; Nora F. Y. Tam; Aijun Yao; Rongliang Qiu; Wai Chin Li; Zhihong Ye (Environmental Science and Pollution Research, 2016)

Sensitivity analysis of crop yields, soil water contents and nitrogen leaching to precipitation, management practices and soil hydraulic properties in semi-arid and humid regions of Canada using the DSSAT model - Wentian He; J. Y. Yang; W. Zhou; C. F. Drury; X. M. Yang; W. D. Reynolds; H. Wang; P. He; Z. T. Li (Nutrient Cycling in Agroecosystems, 2016)

Hippocampal size is related to short-term true and false memory, and right fusiform size is related to long-term true and false memory - Bi Zhu; Chuansheng Chen; Elizabeth F. Loftus; Qinghua He; Xuemei Lei; Qi Dong; Chongde Lin (Brain Structure and Function, 2016)

Two new polyhydroxysterols produced by Fusarium solani , an endophytic fungus from Chloranthus multistachys - W. Y. Shen; R. Bai; A. R. Wang; J. Y. He; H. Wang; Y. Zhang; X. F Zhao; J. Y. Dong (Natural Product Research, 2016)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Characterization, expression analysis and localization pattern of toll‐like receptor 1 ( tlr1 ) and toll‐like receptor 2 ( tlr2 ) genes in grass carp Ctenopharyngodon idella - L. B. He; H. Wang; L. F. Luo; S. H. Jiang; L. Y. Liu; Y. M. Li; R. Huang; L. J. Liao; Z. Y. Zhu; Y. P. Wang (Journal of Fish Biology, 2016)
In this study, the toll‐like receptor 1 ( tlr1 ) and toll‐like receptor 2 ( tlr2 ) genes of grass carp Ctenopharyngodon idella were cloned and characterized. tlr1 and tlr2 were found to be highly expressed in immune system organs such as spleen, middle kidney and heart kidney. The expression level of tlr1 and tlr2 was found to be up‐regulated at the later stage of viral challenge process. Moreover, subcellular localization indicated that Tlr1 and Tlr2 shared similar localization pattern and both of them may locate in the plasma membrane of transfected cells.

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

An inland waterway traffic noise prediction model for environmental assessment in China - B. L. Dai; N. Sheng; Y. L. He; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Association between magnesium intake and risk of colorectal cancer among postmenopausal women - Anna M. Gorczyca; Ka He; Pencheng Xun; Karen L. Margolis; Janet P. Wallace; Dorothy Lane; Cynthia Thomson; Gloria Y. F. Ho; James M. Shikany; Juhua Luo (Cancer Causes & Control, 2015)

A Study of Complete Video-Assisted Thoracoscopic Surgery Lobectomy in Treatment of Elderly Patients with Non-Small Cell Lung Cancer: Curative Effect and Impact on Clinical Prognosis - Y. Xue; Y. Y. Wang; K. Zhang; W. Cong; B. He; F. C. Zeng (Cell Biochemistry and Biophysics, 2015)

Global diversity and taxonomy of the Auricularia auricula-judae complex (Auriculariales, Basidiomycota) - Fang Wu; Yuan Yuan; Shuang-Hui He; Asanka R. Bandara; Kevin D. Hyde; Vera F. Malysheva; De-Wei Li; Yu-Cheng Dai (Mycological Progress, 2015)

A Novel Experimental Technique to Simulate Pillar Burst in Laboratory - M. C. He; F. Zhao; M. Cai; S. Du (Rock Mechanics and Rock Engineering, 2015)

Cytogenetic and molecular identification of a new wheat- Thinopyrum intermedium addition line with resistance to powdery mildew - X.L. Qi; X.F. Li; F. He; L.Q. Hu; Y.G. Bao; J.R. Gao; H.G. Wang (Cereal Research Communications, 2015)

Choline Ameliorates Deficits in Balance Caused by Acute Neonatal Ethanol Exposure - Cynthia F. Bearer; Kristen A. Wellmann; Ningfeng Tang; Min He; Sandra M. Mooney (The Cerebellum, 2015)

Recovery of valuable metal concentrate from waste printed circuit boards by a physical beneficiation technology - J. F. He; C. L. Duan; Y. Q. He; H. J. Zhang (International Journal of Environmental Science and Technology, 2015)

Polymorphisms and DNA methylation level in the CpG site of the GHR1 gene associated with mRNA expression, growth traits and hormone level of half-smooth tongue sole (Cynoglossus semilaevis) - J. L. Zhao; Y. F. Si; F. He; H. S. Wen; J. F. Li; Y. Y. Ren; M. L. Zhao; Z. J. Huang; S. L. Chen (Fish Physiology and Biochemistry, 2015)

Multi‐model and multi‐sensor estimations of evapotranspiration over the Volta Basin, West Africa - S. A. Andam‐Akorful; V. G. Ferreira; J. L. Awange; E. Forootan; X. F. He (International Journal of Climatology, 2015)
The estimation of large‐scale evapotranspiration ( ET ) is complex, and typically relies on the outputs of land surface models ( LSMs ) or remote sensing observations. However, over some regions of Africa, inconsistencies exist between different estimations of ET fluxes, which should be investigated. In this study, we evaluate and combine different ET estimates from moderate‐resolution imaging spectroradiometer ( MODIS ), Global Land Data Assimilation System ( GLDAS ) and terrestrial water budget ( TWB ) approaches over the Volta Basin, West Africa. ET estimates from water balance equation are obtained as residuals from monthly terrestrial water‐storage ( TWS ) changes derived from Gravity Recovery and Climate Experiment ( GRACE ), Tropical Rainfall Measurement Mission ( TRMM )'s rainfall data, and in situ discharge from Akosombo Dam (Ghana). An averaged estimation of ET time series is derived from all the ET estimations under study, while taking into account their uncertainties. The resulting ensemble‐averaged ET was then used to assess each of the individual ET estimates. Overall, out of the seven investigated ET estimates (two from the water balance approach of which one considers water storage using GRACE ‐derived TWS and the other ignoring it, four from GLDAS and one from MODIS ), only MODIS (28.12 mm month –1 ), GLDAS–NOAH (32.74 mm month –1 ) and TWB (32.84 mm month –1 ) were found to represent the range of variability close to the computed averaged reference ET (30.25 mm month –1 ). ET estimations inferred from MODIS were also found to represent relatively lower magnitude of uncertainties, that is, 3.99 mm month –1 over the Volta Basin (cf. 7.06 and 18.85 mm month –1 for GLDAS‐NOAH and TWB ‐based ET estimations, respectively).

Molecular cloning and characterization of gonadotropin subunits (GTHα, FSHβ and LHβ) and their regulation by hCG and GnRHa in Japanese sea bass (Lateolabrax japonicas) in vivo - Mei L. Chi; Meng Ni; Ji F. Li; Feng He; Kun Qian; Pei Zhang; Sen H. Chai; Hai S. Wen (Fish Physiology and Biochemistry, 2015)

Simulation of long-term spring wheat yields, soil organic C, N and water dynamics using DSSAT-CSM in a semi-arid region of the Canadian prairies - Zhuo Ting Li; J. Y. Yang; W. N. Smith; C. F. Drury; R. L. Lemke; B. Grant; W. T. He; Xiao Gang Li (Nutrient Cycling in Agroecosystems, 2015)

Analysis of Bordetella pertussis clinical isolates circulating in European countries during the period 1998–2012 - M. van Gent; C. J. Heuvelman; H. G. van der Heide; H. O. Hallander; A. Advani; N. Guiso; C. H. Wirsing von Kőnig; D. F. Vestrheim; T. Dalby; N. K. Fry; D. Pierard; L. Detemmerman; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

The relative importance of climate change and shrub encroachment on nocturnal warming in the southwestern United States - Yufei He; Paolo D'Odorico; Stephan F. J. De Wekker (International Journal of Climatology, 2015)
Many regions of the world are affected by a major land cover change resulting from the encroachment of woody plants and the conversion of grasslands into shrublands. In the southwestern United States, such a change in vegetation cover has been found to increase the winter nighttime temperature, thereby contributing to a positive feedback between shrub encroachment and microclimate in areas encroached by cold‐sensitive shrubs. Temperature measurements show that winter minimum temperatures are on average ∼2 K higher in shrubland than in adjacent grassland sites. It is unclear how the nighttime warming induced by shrub encroachment compares with regional climate trends. We address this question by analysing both the historical and future regional temperature trends in central New Mexico. The estimated regional increase in minimum winter temperature ranges from 1 to 4 K per century using observations and climate models. Thus, the warming resulting from shrub encroachment is equivalent to a change in regional climate over a time period of century scale, which suggests that shrub encroachment has an overall important effect on the regional climate.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Identification and molecular characterization of two begomoviruses from Pouzolzia zeylanica (L.) Benn. exhibiting yellow mosaic symptoms in adjacent regions of China and Vietnam - Y. F. Tang; Z. G. Du; Z. F. He; Judith K. Brown; X. M. She (Archives of Virology, 2014)

Re-evaluation of the inheritance for root-knot nematode resistance in the Upland cotton germplasm line M-120 RNR revealed two epistatic QTLs conferring resistance - Yajun He; Pawan Kumar; Xinlian Shen; Richard F. Davis; Guillermo Van Becelaere; O. Lloyd May; Robert L. Nichols; Peng W. Chee (Theoretical and Applied Genetics, 2014)

Safety of combination therapy with milrinone and esmolol for heart protection during percutaneous coronary intervention in acute myocardial infarction - Kian-Keong Poh; Xin Xu; Mark Y. Chan; Chi-Hang Lee; Edgar L. Tay; Adrian F. Low; Koo Hui Chan; Winnie Sia; Liang-Qiu Tang; Huay Cheem Tan; Charles Y. Lui; Vincent Nguyen; et al. (European Journal of Clinical Pharmacology, 2014)

Introduction to the thematic issue “From brain function to therapy” - Perry F Bartlett; RongQiao He (Science China Life Sciences, 2014)

Transcriptome profile of human neuroblastoma cells in the hypomagnetic field - WeiChuan Mo; Ying Liu; Perry F Bartlett; RongQiao He (Science China Life Sciences, 2014)

The role of the N-methyl-d-aspartate receptor in the proliferation of adult hippocampal neural stem and precursor cells - Chanel J. Taylor; RongQiao He; Perry F. Bartlett (Science China Life Sciences, 2014)

Visualizing the microtubule-associated protein tau in the nucleus - Jing Lu; Ting Li; RongQiao He; Perry F. Bartlett; Jürgen Götz (Science China Life Sciences, 2014)

Reuse of dewatered sewage sludge conditioned with skeleton builders as landfill cover material - Y. L. Li; J. W. Liu; J. Y. Chen; Y. F. Shi; W. Mao; H. Liu; Y. Li; S. He; J. K. Yang (International Journal of Environmental Science and Technology, 2014)

Cloning and expression analysis of Foxl2 during the reproductive cycle in Korean rockfish, Sebastes schlegeli - Wei J. Mu; Hai S. Wen; Ji F. Li; Feng He (Fish Physiology and Biochemistry, 2013)

Recruitment limitation of dominant tree species with varying seed masses in a subtropical evergreen broad-leaved forest - Y. Luo; F. He; S. Yu (Community Ecology, 2013)

The new sequencer on the block: comparison of Life Technology’s Proton sequencer to an Illumina HiSeq for whole-exome sequencing - Joseph F. Boland; Charles C. Chung; David Roberson; Jason Mitchell; Xijun Zhang; Kate M. Im; Ji He; Stephen J. Chanock; Meredith Yeager; Michael Dean (Human Genetics, 2013)

Molecular characterization of a novel monopartite begomovirus isolated from Pouzolzia zeylanica in China - Y. F. Tang; Z. G. Du; Z. F. He; X. M. She; J. H. Cai (Archives of Virology, 2013)

Cloning and expression analysis of follicle-stimulating hormone and luteinizing hormone receptor during the reproductive cycle in Korean rockfish (Sebastes schlegeli) - Wei J. Mu; Hai S. Wen; Feng He; Ji F. Li; Miao Liu; Yuan Q. Zhang; Jian Hu; Bao X. Qi (Fish Physiology and Biochemistry, 2013)

Vegetation–microclimate feedbacks in woodland–grassland ecotones - Paolo D'Odorico; Yufei He; Scott Collins; Stephan F. J. De Wekker; Vic Engel; Jose D. Fuentes (Global Ecology and Biogeography, 2013)
Aim Climatic conditions exert a strong control on the geographic distribution of many woodland‐to‐grassland transition zones (or ‘tree lines’). Because woody plants have, in general, a weaker cold tolerance than herbaceous vegetation, their altitudinal or latitudinal limits are strongly controlled by cold sensitivity. While temperature controls on the dynamics of woodland–grassland ecotones are relatively well established, the ability of woody plants to modify their microclimate and to create habitat for seedling establishment and growth may involve a variety of processes that are still not completely understood. Here we investigate feedbacks between vegetation and microclimatic conditions in the proximity to woodland–grassland ecotones. Location We concentrate on arctic and alpine tree lines, the transition between mangrove forests and salt marshes in coastal ecosystems, and the shift from shrubland to grassland along temperature gradients in arid landscapes. Methods We review the major abiotic and biotic mechanisms underlying the ability of woody plants to alter the nocturnal microclimate by increasing the temperatures they are exposed to. Results We find that in many arctic, alpine, desert and coastal landscapes the presence of trees or shrubs causes nocturnal warming thereby favouring the establishment and survival of woody plants. Main conclusion Because of this feedback, trees and shrubs may establish in areas that would be otherwise unsuitable for their survival. Thus, in grassland–woodland transition zones both vegetation covers may be (alternative) stable states of the landscape, thereby affecting the way tree lines may migrate in response to regional and global climate change.

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

The separation mechanism and application of a tapered diameter separation bed - Y. M. Zhao; C. L. Duan; L. L. Wu; H. J. Zhang; J. F. He; Y. Q. He (International Journal of Environmental Science and Technology, 2012)

Ischemic Preconditioning Attenuates Brain Edema After Experimental Intracerebral Hemorrhage - Yangdong He; Murat Karabiyikoglu; Ya Hua; Richard F. Keep; Guohua Xi (Translational Stroke Research, 2012)

Molecular cloning, characterization expression of P450c17-I and P450c17-II and their functions analysis during the reproductive cycle in males of barfin flounder (Verasper moseri) - Guo X. Jin; Hai S. Wen; Feng He; Ji F. Li; Cai F. Chen; Jia R. Zhang; Xiao Y. Chen; Bao Shi; Dan Shi; Yan P. Yang; Bao X. Qi; Na Li (Fish Physiology and Biochemistry, 2012)

Prevalence of Puroindoline D1 and Puroindoline b-2 variants in U.S. Pacific Northwest wheat breeding germplasm pools, and their association with kernel texture - Hongwei Geng; Brian S. Beecher; Zhonghu He; Alecia M. Kiszonas; Craig F. Morris (Theoretical and Applied Genetics, 2012)

Polymorphisms of STAT5A gene and their association with milk production traits in Holstein cows - X. He; M. X. Chu; L. Qiao; J. N. He; P. Q. Wang; T. Feng; R. Di; G. L. Cao; L. Fang; Y. F. An (Molecular Biology Reports, 2012)

Value of measuring muscle performance to assess changes in lean mass with testosterone and growth hormone supplementation - E. Todd Schroeder; Jiaxiu He; Kevin E. Yarasheski; Ellen F. Binder; Carmen Castaneda-Sceppa; Shalender Bhasin; Christina M. Dieli-Conwright; Miwa Kawakubo; Ronenn Roubenoff; Stanley P. Azen; Fred R. Sattler (European Journal of Applied Physiology, 2012)

Extraction of spatial-temporal rules from mesoscale eddies in the South China Sea based on rough set theory - Y. Du; X. Fan; Z. He; F. Su; C. Zhou; H. Mao; D. Wang (Ocean Science, 2011)
In this paper, a rough set theory is introduced to represent spatial-temporal relationships and extract the corresponding rules from typical mesoscale-eddy states in the South China Sea (SCS). Three decision attributes are adopted in this study, which make the approach flexible in retrieving spatial-temporal rules with different features. The results demonstrate that this approach is effective, and therefore provides a powerful approach to forecasts in the future studies. Spatial-temporal rules in the SCS indicate that warm eddies following the rules are generally in the southeastern and central SCS around 2000 m isobaths in winter. Their intensity and vorticity are weaker than those of cold eddies. They usually move a shorter distance. By contrast, cold eddies are in 2000 m and deeper regions of the southwestern and northeastern SCS in spring and fall. Their intensity and vorticity are strong. Usually they move a long distance. In winter, a few rules are followed by cold eddies in the northern tip of the basin and southwest of Taiwan Island rather than warm eddies, indicating cold eddies may be well-regulated in the region. Several warm-eddy rules are achieved west of Luzon Island, indicating warm eddies may be well-regulated in the region as well. Otherwise, warm and cold eddies are distributed not only in the jet flow off southern Vietnam induced by intraseasonal wind stress in summer-fall, but also in the northern shallow water, which should be a focus of a future study.

Developmental profile of storage reserve accumulation in soybean somatic embryos - Yan He; Tammie E. Young; Karen Rebecca Clark; Kathryn F. Kleppinger-Sparace; William C. Bridges; Salvatore A. Sparace (In Vitro Cellular & Developmental Biology - Plant, 2011)

Identification of amino acids in highly pathogenic avian influenza H5N1 virus hemagglutinin that determine avian influenza species specificity - Zheng Li; Zhonghua Liu; Chi Ma; Linqi Zhang; Yuelong Su; George F. Gao; Zi Li; Lianxian Cui; Wei He (Archives of Virology, 2011)

EmmdR, a new member of the MATE family of multidrug transporters, extrudes quinolones from Enterobacter cloacae - Gui-Xin He; Conner Thorpe; Dennis Walsh; Robert Crow; Huizhong Chen; Sanath Kumar; Manuel F. Varela (Archives of Microbiology, 2011)

Mechanisms of chloride in cardiomyocyte anoxia-reoxygenation injury: the involvement of oxidative stress and NF-kappaB activation - D. Liu; H. He; G. L. Li; J. Chen; D. Yin; Z. P. Liao; L. Tang; Q. R. Huang; Z. F. Lai; M. He (Molecular and Cellular Biochemistry, 2011)

Using the DSSAT-CERES-Maize model to simulate crop yield and nitrogen cycling in fields under long-term continuous maize production - H. L. Liu; J. Y. Yang; C. F. Drury; W. D. Reynolds; C. S. Tan; Y. L. Bai; P. He; J. Jin; G. Hoogenboom (Nutrient Cycling in Agroecosystems, 2011)

Degradation of fluoranthene by a newly isolated strain of Herbaspirillum chlorophenolicum from activated sludge - Hong X. Xu; Hai Y. Wu; Yu P. Qiu; Xiao Q. Shi; Gen H. He; Jing F. Zhang; Ji C. Wu (Biodegradation, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Cloning and expression of P450c17-I (17α-hydroxylase/17,20-lyase) in brain and ovary during gonad development in Cynoglossus semilaevis - Cai F. Chen; Hai S. Wen; Zhao P. Wang; Feng He; Jia R. Zhang; Xiao Y. Chen; Guo X. Jin; Bao Shi; Dan Shi; Yan P. Yang; Ji F. Li; Bao X. Qi; et al. (Fish Physiology and Biochemistry, 2010)

Fine mapping QMi-C11 a major QTL controlling root-knot nematodes resistance in Upland cotton - Xinlian Shen; Yajun He; Edward L. Lubbers; Richard F. Davis; Robert L. Nichols; Peng W. Chee (Theoretical and Applied Genetics, 2010)

Characterization of conformation-specific monoclonal antibodies against rabies virus nucleoprotein - Yan Jiang; Yonghuang Luo; Frank Michel; Robert J. Hogan; Ying He; Zhen F. Fu (Archives of Virology, 2010)

Taxonomic identity, phylogeny, climate and soil fertility as drivers of leaf traits across Chinese grassland biomes - Jin-Sheng He; Xiangping Wang; Bernhard Schmid; Dan F. B. Flynn; Xuefei Li; Peter B. Reich; Jingyun Fang (Journal of Plant Research, 2010)

Matched pairs of human prostate stromal cells display differential tropic effects on LNCaP prostate cancer cells - Xiaojuan Sun; Hui He; Zhihui Xie; Weiping Qian; Haiyen E. Zhau; Leland W. K. Chung; Fray F. Marshall; Ruoxiang Wang (In Vitro Cellular & Developmental Biology - Animal, 2010)

Occurrence of Aliphatic Hydrocarbons in Water, Suspended Particulate Matter and Sediments of Daliao River System, China - W. Guo; M. C. He; Z. F. Yang; C. Y. Lin; X. C. Quan (Bulletin of Environmental Contamination and Toxicology, 2010)

Determinants of the geographical extent of invasive plants in China: effects of biogeographical origin, life cycle and time since introduction - Qiao Q. Huang; Chen Qian; Yu Wang; Xin Jia; Xin F. Dai; Hao Zhang; Fei He; Shao L. Peng; Gen X. Wang (Biodiversity and Conservation, 2010)

Genome-wide profiling of histone H3 lysine 9 acetylation and dimethylation in Arabidopsis reveals correlation between multiple histone marks and gene expression - Junli Zhou; Xiangfeng Wang; Kun He; Jean-Benoit F. Charron; Axel A. Elling; Xing Wang Deng (Plant Molecular Biology, 2010)

The rag locus of Porphyromonas gingivalis might arise from Bacteroides via horizontal gene transfer - Z. Su; F. Kong; S. Wang; J. Chen; R. Yin; C. Zhou; Y. Zhang; Z. He; Y. Shi; Y. Xue; X. Shi; L. Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Brain Alpha- and Beta-Globin Expression after Intracerebral Hemorrhage - Yangdong He; Ya Hua; Jin-Yul Lee; Wenquan Liu; Richard F. Keep; Michael M. Wang; Guohua Xi (Translational Stroke Research, 2010)

Polar lipid remodeling and increased sulfatide expression are associated with the glioma therapeutic candidates, wild type p53 elevation and the topoisomerase-1 inhibitor, Irinotecan - Huan He; Carol L. Nilsson; Mark R. Emmett; Yongjie Ji; Alan G. Marshall; Roger A. Kroes; Joseph R. Moskal; Howard Colman; Frederick F. Lang; Charles A. Conrad (Glycoconjugate Journal, 2010)

Taxonomic, phylogenetic, and environmental trade‐offs between leaf productivity and persistence - Jin-Sheng He; Xiangping Wang; Dan F. B. Flynn; Liang Wang; Bernhard Schmid; Jingyun Fang (Ecology, 2009)
Assessing the influence of climate, soil fertility, and species identity on leaf trait relationships is crucial for understanding the adaptations of plants to their environment and for interpreting leaf trait relationships across spatial scales. In a comparative field study of 171 plant species in 174 grassland sites across China, we examined the trade‐offs, defined as negative covariance between two traits, between leaf persistence (leaf mass per area, LMA) and leaf productivity (mass‐based photosynthetic rate, A mass , N and P content, and photosynthetic N use efficiency, PNUE). We asked to which extent these trade‐offs were influenced by: (1) variation among sites within species, decomposed into variation due to climatic and soil variables; (2) variation among species within sites, decomposed into variation among taxonomic, functional, or phylogenetic groups; and (3) the joint contribution of variation among species and sites. We used mixed‐model analysis of covariance to partition bivariate relationships between leaf traits into trade‐off components. We found significant mass‐based persistence–productivity trade‐offs of LMA– A mass , LMA–N, LMA–P, and LMA–PNUE consistent with previous broadscale findings. Overall, (1) variation among sites within species explained 14–23%, (2) variation among species within sites explained 20–34%, and (3) the two together explained 42–63% of the total covariance between leaf traits. Interspecific trade‐offs of LMA– A mass , LMA–N, and LMA–P were stronger than inter‐site ones. A relatively low amount of covariance was explained by climatic and soil variables. However, we found the trade‐offs were stronger for LMA–N and LMA–P at higher precipitation and for LMA–PNUE at greater soil fertility, if displayed by major axis regression, which combined both intra‐ and interspecific variation. Residual trade‐offs within species and sites were weak, suggesting that intraspecific, intra‐site variation in physiology was less important than variation imposed by species identity or environmental differences among sites. Our results from grassland biomes add evidence for the fundamental nature of productivity–persistence trade‐offs in plants. No individual factor emerged as the single major cause for these trade‐offs. Rather, the total covariance between leaf traits was explained by a combination of factors, each contributing a range of explanatory power.

Molecular characterization of a distinct begomovirus infecting Allamanda cathartica in Guangdong, China - Z. F. He; M. J. Mao; H. Yu; H. P. Li; X. Chen (Archives of Virology, 2009)

Characterization of Cadmium Uptake and Translocation in a Cadmium-Sensitive Mutant of Rice (Oryza sativa L. ssp. japonica) - J. Y. He; Y. F. Ren; F. J. Wang; X. B. Pan; C. Zhu; D. A. Jiang (Archives of Environmental Contamination and Toxicology, 2009)

Characterization of plant-derived water extractable organic matter by multiple spectroscopic techniques - Zhongqi He; Jingdong Mao; C. Wayne Honeycutt; Tsutomu Ohno; James F. Hunt; Barbara J. Cade-Menun (Biology and Fertility of Soils, 2009)

Numerical simulation of the anthropogenic heat effect on urban boundary layer structure - Y. Chen; W. M. Jiang; N. Zhang; X. F. He; R. W. Zhou (Theoretical and Applied Climatology, 2009)

Reflectance measures of grassland biophysical structure - Yuhong He; Xulin Guo; J. F. Wilmshurst (International Journal of Remote Sensing, 2009)

Cloning and phylogenetic analysis of polyphenol oxidase genes in common wheat and related species - X. Y. He; Z. H. He; C. F. Morris; X. C. Xia (Genetic Resources and Crop Evolution, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Variation of atmospheric aerosol optical depth and its relationship with climate change in China east of 100°E over the last 50 years - L.-X. Chen; B. Zhang; W.-Q. Zhu; X.-J. Zhou; Y.-F. Luo; Z.-J. Zhou; J.-H. He (Theoretical and Applied Climatology, 2009)

Distribution of the photoperiod insensitive Ppd-D1a allele in Chinese wheat cultivars - F. P. Yang; X. K. Zhang; X. C. Xia; D. A. Laurie; W. X. Yang; Z. H. He (Euphytica, 2009)

Molecular mapping of leaf rust resistance gene LrZH84 in Chinese wheat line Zhou 8425B - X. L. Zhao; T. C. Zheng; X. C. Xia; Z. H. He; D. Q. Liu; W. X. Yang; G. H. Yin; Z. F. Li (Theoretical and Applied Genetics, 2008)

High frequency plant regeneration from mature embryo explants of highland barley (Hordeum vulgare L. var. nudum Hk. f.) under endosperm-supported culture - T. He; J. F. Jia (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Leaf nitrogen:phosphorus stoichiometry across Chinese grassland biomes - Jin-Sheng He; Liang Wang; Dan F. B. Flynn; Xiangping Wang; Wenhong Ma; Jingyun Fang (Oecologia, 2008)

Cloning and characterization of a novel low molecular weight glutenin subunit gene at the Glu-A3 locus from wild emmer wheat (Triticum turgidum L. var. dicoccoides) - Xiaohui Li; Aili Wang; Yinghua Xiao; Yueming Yan; Zhonghu He; Rudi Appels; Wujun Ma; S. L. K. Hsam; F. J. Zeller (Euphytica, 2008)

Inhibition of phosphorus sorption to goethite, gibbsite, and kaolin by fresh and decomposed organic matter - James F. Hunt; Tsutomu Ohno; Zhongqi He; C. Wayne Honeycutt; D. Bryan Dail (Biology and Fertility of Soils, 2007)

Assessing the effect of land use/land cover change on the change of urban heat island intensity - J. F. He; J. Y. Liu; D. F. Zhuang; W. Zhang; M. L. Liu (Theoretical and Applied Climatology, 2007)

Old comb for nesting site recognition by Apis dorsata? Field experiments in China - F. Liu; D. W. Roubik; D. He; J. Li (Insectes Sociaux, 2007)

Y chromosomes of prehistoric people along the Yangtze River - Hui Li; Ying Huang; Laura F. Mustavich; Fan Zhang; Jing-Ze Tan; Ling-E Wang; Ji Qian; Meng-He Gao; Li Jin (Human Genetics, 2007)

Cytogenetic studies on two F1 hybrids of autotetraploid rice varieties showing extremely high level of heterosis - L. Luan; S. B. Tu; W. B. Long; X. Wang; Y. H. Liu; F. L. Kong; T. He; W. G. Yan; M. Q. Yu (Plant Systematics and Evolution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reusable immunomagnetic beads in an enzyme immunoassay - F. C. Han; J. Luo; H. F. Guo; W. H. Zhang; D. C. He; X. J. Yan (World Journal of Microbiology and Biotechnology, 2007)

Complete nucleotide sequence of rice gall dwarf virus genome segment S7 - F. X. Liu; X. L. Ruan; Y. W. He; H. P. Li; J. S. Hu (Archives of Virology, 2007)

Allelic variation of polyphenol oxidase (PPO) genes located on chromosomes 2A and 2D and development of functional markers for the PPO genes in common wheat - X. Y. He; Z. H. He; L. P. Zhang; D. J. Sun; C. F. Morris; E. P. Fuerst; X. C. Xia (Theoretical and Applied Genetics, 2007)

Characteristics and Source Identification of Particulate Matter in Wintertime in Beijing - F. K. Duan; X. D. Liu; K. B. He; Y. W. Li; S. P. Dong (Water, Air, & Soil Pollution, 2007)

Isolation of Endophytic Actinomycetes from Different Cultivars of Tomato and their Activities Against Ralstonia solanacearum in Vitro - H. M. Tan; L. X. Cao; Z. F. He; G. J. Su; B. Lin; S. N. Zhou (World Journal of Microbiology and Biotechnology, 2006)

Energy Density of Lake Whitefish Coregonus clupeaformis in Lakes Huron and Michigan - Steven A. Pothoven; Thomas F. Nalepa; Charles P. Madenjian; Richard R. Rediske; Philip J. Schneeberger; Ji X. He (Environmental Biology of Fishes, 2006)

Selection of Interspecific Hybrids for Anther Culture of Indica Rice - T. He; Y. Yang; S. B. Tu; M. Q. Yu; X. F. Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Stoichiometry and large-scale patterns of leaf carbon and nitrogen in the grassland biomes of China - Jin-Sheng He; Jingyun Fang; Zhiheng Wang; Dali Guo; Dan F. B. Flynn; Zhi Geng (Oecologia, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Molecular mapping of stripe rust resistance gene YrCH42 in Chinese wheat cultivar Chuanmai 42 and its allelism with Yr24 and Yr26 - G. Q. Li; Z. F. Li; W. Y. Yang; Y. Zhang; Z. H. He; S. C. Xu; R. P. Singh; Y. Y. Qu; X. C. Xia (Theoretical and Applied Genetics, 2006)

Molecular tagging of stripe rust resistance gene YrZH84 in Chinese wheat line Zhou 8425B - Z. F. Li; T. C. Zheng; Z. H. He; G. Q. Li; S. C. Xu; X. P. Li; G. Y. Yang; R. P. Singh; X. C. Xia (Theoretical and Applied Genetics, 2006)

Molecular and biochemical characterization of puroindoline a and b alleles in Chinese landraces and historical cultivars - F. Chen; Z. H. He; X. C. Xia; L. Q. Xia; X. Y. Zhang; M. Lillemo; C. F. Morris (Theoretical and Applied Genetics, 2006)

Tuning in to the Amazing Outer Hair Cell: Membrane Wizardry with a Twist and Shout - D.Z.Z. He; J. Zheng; F. Kalinec; S. Kakehata; J. Santos-Sacchi (The Journal of Membrane Biology, 2006)

The Mitochondrial Genome of Xiphinema americanum sensu stricto (Nematoda: Enoplea): Considerable Economization in the Length and Structural Features of Encoded Genes - Y. He; J. Jones; M. Armstrong; F. Lamberti; M. Moens (Journal of Molecular Evolution, 2005)

Multilevel Nonlinear Mixed-Effects Models for the Modeling of Earlywood and Latewood Microfibril Angle - Lewis Jordan; Richard F. Daniels; Alexander Clark; Rechun He (Forest Science, 2005)
Earlywood and latewood microfibril angle (MFA) was determined at 1-millimeter intervals from disks at 1.4 meters, then at 3-meter intervals to a height of 13.7 meters, from 18 loblolly pine (Pinus taeda L.) trees grown in southeastern Texas. A modified three-parameter logistic function with mixed effects is used for modeling earlywood and latewood MFA. By making the parameters of the logistic function linear functions of height, a three-dimensional model was developed that describes the changes of earlywood and latewood MFA within the tree. A first-order autoregressive correlation structure and a variance model corresponding to a variance covariate given by the fitted values for each wood type, but in which the proportionality constant differs according to the level of wood type, was identified as the within-group correlation and variance structures. Cross-validation was used to determine model accuracy and precision. The methods of model development including determination of the height structure, which parameters should be considered random or fixed, determination of an appropriate variance-covariance structure, and prediction are addressed. Model performance was evaluated utilizing informative statistics including likelihood ratio tests (LRTs), Akaike information criterion (AIC), and Bayesian information criterion (BIC). FOR. SCI. 51(4):357–371.

Differential drought responses between saplings and adult trees in four co-occurring species of New England - Jin-Sheng He; Qi-Bin Zhang; F. A. Bazzaz (Trees, 2005)

In Situ Thermal Denaturation of Proteins in Dunning AT-1 Prostate Cancer Cells: Implication for Hyperthermic Cell Injury - Xiaoming He; Willem F. Wolkers; John H. Crowe; David J. Swanlund; John C. Bischof (Annals of Biomedical Engineering, 2004)

Semiochemistry of the Goldeneyed Lacewing Chrysopa oculata: Attraction of Males to a Male-Produced Pheromone - Qing-He Zhang; Kamlesh R. Chauhan; Eric F. Erbe; Ajay R. Vellore; Jeffrey R. Aldrich (Journal of Chemical Ecology, 2004)

Effects of salinity on growth and compatible solutes of callus induced from Populus euphratica - F. Zhang; Y. L. Yang; W. L. He; X. Zhao; L. X. Zhang (In Vitro Cellular & Developmental Biology - Plant, 2004)

Primary Investigation of Heavy Metal Contamination Status in Mollusks Collected from Chinese Coastal Sites - L.-N. Liang; J.-T. Hu; D.-Y. Chen; Q.-F. Zhou; B. He; G.-B. Jiang (Bulletin of Environmental Contamination and Toxicology, 2004)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

Inhibition of Serine Palmitoyltransferase by Myriocin, a Natural Mycotoxin, Causes Induction of C-Myc in Mouse Liver - Quanren He; Victor J. Johnson; Marcin F. Osuchowski; Raghubir P. Sharma (Mycopathologia, 2004)

Isolation and characterization of rice mutants compromised in Xa21-mediated resistance to X. oryzae pv. oryzae - G. L. Wang; C. Wu; L. Zeng; C. He; M. Baraoidan; F. de Assis Goes da Silva; C. E. Williams; P. C. Ronald; H. Leung (Theoretical and Applied Genetics, 2004)

Concentration Level of Fine Airborne Lead in Beijing, People?s Republic of China - K. B. He; F. K. Duan; Y. L. Ma; F. M. Yang; Q. Zhang; X. C. Yu; S. Cadle; T. Chan; Y. Yan; P. Mulawa (Bulletin of Environmental Contamination and Toxicology, 2004)

Genomic characterization of Rim2 / Hipa elements reveals a CACTA-like transposon superfamily with unique features in the rice genome - G.-D. Wang; P.-F. Tian; Z.-K. Cheng; G. Wu; J.-M. Jiang; D.-B. Li; Q. Li; Z.-H. He (Molecular Genetics and Genomics, 2003)

Canine Imerslund-Grsbeck syndrome maps to a region orthologous to HSA14q - Qianchuan He; John C. Fyfe; Alejandro A. Schffer; Adam Kilkenney; Petra Werner; Ewen F. Kirkness; Paula S. Henthorn (Mammalian Genome, 2003)

X-ray structure of methanol dehydrogenase from Paracoccus denitrificans and molecular modeling of its interactions with cytochrome c-551i - Zong-Xiang Xia; Wei-Wen Dai; Yong-Ning He; Scott A. White; F. Scott Mathews; Victor L. Davidson (JBIC Journal of Biological Inorganic Chemistry, 2003)

Buckwheat (Fagopyrum esculentum Moench) has high capacity to take up phosphorus (P) from a calcium (Ca)-bound Source - Y-G Zhu; Y-Q He; S E Smith; F A Smith (Plant and Soil, 2002)

Phylogenetic relationships of the Magnoliaceae inferred from cpDNA matK sequences - S. Shi; H. Jin; Y. Zhong; X. He; Y. Huang; F. Tan; D. E. Boufford (Theoretical and Applied Genetics, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Design of minimax robust filtering for an integrated GPS/INS system - X. F. He; Y. Q. Chen; B. Vik (Journal of Geodesy, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Functional studies on the anti-pathoangiogenic properties of CM101 - He-Ping Yan; Clint E. Carter; En-ze Wang; David L. Page; Kay Washington; Barbara D. Wamil; F. Michael Yakes; Gary B. Thurman; Carl G. Hellerqvist (Angiogenesis, 1998)

A new approach to enhance growth and nodulation of Acacia mangium through aeroponic culture - F. Martin-Laurent; S.-K. Lee; F.-Y. Tham; J. He; H. G. Diem; P. Durand (Biology and Fertility of Soils, 1997)

Kinetics of reversible N-ethylmaleimide alkylation of metallothionein and the subsequent metal release - C. F. Shaw III.; Libin He; Amalia Muñoz; M. Meral Savas; Susan Chi; Cynthia L. Fink; Tong Gan; David H. Petering (JBIC Journal of Biological Inorganic Chemistry, 1997)